Caesarean Section and Perinatal Outcome in a Sub-urban Tertiary Hospital in Northwest Nigeria - Ugwa, EA; Ashimi, AO; Abubakar, MY (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: This study was undertaken to review the caesarean section rate and perinatal mortality in Federal Medical Centre, Birnin Kudu from 1 January 2010 to 31 December 2012. Methods: This was a retrospective study involving review of 580 case files. Ethical clearance was obtained. The records of labour ward, neonatal intensive care unit and operating theatre were use. Information extracted includes age, parity, booking status, total deliveries, indications for caesarean section and perinatal outcome from 1st January 2010 to 31st December 2012 at Federal Medical Centre, Birnin Kudu. The data obtained was analyzed using SPSS version 16.0 statistical software (Chicago). Absolute numbers and simple percentages were used to describe categorical variables. Results: A total of 590 caesarean sections were done which is rate of 17.69%. Of the 590 caesarean deliveries, 580 case notes were retrieved giving a retrieval rate of 98.3%. A total of 96 out of 580 babies died within the first one week of caesarean delivery, giving a perinatal mortality rate of 17.4 per 1000. The average age of the women was 25.9±6.2 years. Majority of them were uneducated and unemployed. Obstructed labour was the most common indication for emergency caesarean section accounting for 31.7% of caesarean sections followed by pre-eclampsia/eclampsia. Conclusions: Caesarean section rate in the present study is comparatively high and perinatal mortality is low but it is unclear if there is a correlation between caesarean section rate and perinatal mortality. This needs further studies.